Strategi Inovasi dan Kinerja UMKM Berbasis Agribisnis di Bandar Lampung - Fadila Marga Saty; Bina Unteawati; Marlinda Apriyani (Jurnal Ilmiah ESAI, 2010)
Product or process innovation and development are some of important requirements of strategy, because every company (both small scale and big scale company) should be able to increase technology, knowledge, exploring capacity as well as control the market based on those ideas and at the end could increase the company performance. The important effect of product innovation to company performance, in this case financial performance, will be the point in this research. Regression model approach is used to view the relation between company performance and innovation strategy type. The purpose of the research is to analyze the influence of regression analysis approach of innovation strategy variable all together to financial performance of Small and Middle Scale Business in agribusiness in Bandar Lampung. Hypothesis proposed in the research is that innovation strategy dimension will influence the financial performance of small and middle scale business. The result showed that innovation strategy positively affected Net Profit Margin variable but not too significant for 58% and only product innovation variable that has significant contribution. Innovation strategy has 32.5% to growth variable in sales, while the most significant variables are innovation process and investment. Innovation strategy has insignificant influence for 5.4 % to return on asset variable.Key words: Innovation Strategy, Performance, Small and Middle Scale Company